2022
DOI: 10.1111/josi.12538
|View full text |Cite
|
Sign up to set email alerts
|

Is protecting older adults from COVID‐19 ageism? A comparative cross‐cultural constructive grounded theory from the United Kingdom and Colombia

Abstract: The COVID-19 pandemic impacted people's lives all over the world, requiring health and safety measures intended to stop the virus from spreading. This study explores whether an unintended consequence of these measures is a new form of ageism. We explore, using qualitative methods, the experiences of older adults living through the pandemic in the United Kingdom and Colombia. Although there were some small differences between countries, for the most part, the experiences were similar. We found that older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…As far as the COVID‐pandemic is concerned, Italy was the first European nation hit by the virus and among the most affected countries in the world (Cesari & Proietti, 2020 ). Furthermore, Italy was the first European country to adopt restrictive measures, with the government imposing the lockdown to the entire country few weeks after the first case diagnosed in mid‐February 2020 (Delmastro & Zamariola, 2020 ). However, the infection and death rates have increased, challenging the public health system severely.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the COVID‐pandemic is concerned, Italy was the first European nation hit by the virus and among the most affected countries in the world (Cesari & Proietti, 2020 ). Furthermore, Italy was the first European country to adopt restrictive measures, with the government imposing the lockdown to the entire country few weeks after the first case diagnosed in mid‐February 2020 (Delmastro & Zamariola, 2020 ). However, the infection and death rates have increased, challenging the public health system severely.…”
Section: The Present Researchmentioning
confidence: 99%
“…However, the infection and death rates have increased, challenging the public health system severely. Italian population profoundly changed their habits and lifestyle, and was hardly impacted by the pandemic on a personal, social, psychological, and economic level (Delmastro & Zamariola, 2020 ; Marazziti et al., 2020 ), with the health care practitioners, disabled persons, caregivers, and older sick patients experiencing negative consequence more severely (Marazziti et al., 2020 ). With a focus on older adults, Italy was among the countries that, facing the possibility of healthcare system collapse, discussed and even adopted an age criterion for the allocation of the scarce health resources, prioritizing the treatment of younger patients (Cesari & Proietti, 2020 ; Fraser et al., 2020 ).…”
Section: The Present Researchmentioning
confidence: 99%
“…For example, older individuals may be treated as lacking independence and spoken to in oversimplified or patronizing ways (Giles & Ogay, 2007 ; Nelson, 2005 ; Ryan et al., 1995 ). In the context of the pandemic, this may also have included well‐intentioned helping behaviors that signaled to older people that they are dependent and helpless (Derrer‐Merk et al., 2022 ; McDarby et al., 2022 ; Monahan et al., 2020 ; Ng et al., 2022 ). Research has shown that these type of behaviors (i.e., benevolent ageism) negatively affect the health, well‐being and autonomy of older adults (Baltes & Wahl, 1996 ; Cary et al., 2017 ; Derrer‐Merk et al., 2022 ; Langer & Rodin, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, researchers, gerontologists, and public health officials have raised concerns about ageism toward older adults including rising rates of abuse (economic, physical, psychological, and sexual), discrimination (in employment and healthcare) and negative depictions of older adults (Ayalon & Tesch‐Roemer, 2018 ; Levy et al., 2020 ; Levy & Macdonald, 2016 ; Lytle et al., 2022 ; Nelson, 2016 ; Palmore, 1990 ). Older adults have often been portrayed negatively as senile, sickly, and a burden on families, healthcare, the economy, and society as a whole in countries such as Canada, China, Colombia, Israel, the United Kingdom, and the United States (Abrams et al., 2015 ; Bai et al., 2016 ; Cohn‐Schwartz & Ayalon, 2021 ; Derrer‐Merk et al., 2022 ; Levy & Apriceno, 2019 ; North & Fiske, 2013b ; Ramírez et al., 2019 ; Sutter et al., 2022 ; WHO, 2021 ).…”
Section: Introductionmentioning
confidence: 99%